2004
DOI: 10.1021/ic049861p
|View full text |Cite
|
Sign up to set email alerts
|

XAFS and LIBD Investigation of the Formation and Structure of Colloidal Pu(IV) Hydrolysis Products

Abstract: Pu(IV) oxyhydroxide colloid growth is investigated with XAFS and LIBD. From combined results a model of colloid formation is proposed, which leads to a face-centered cubic Pu sublattice having cation defects, as observed with EXAFS, and a linear dependency of log [Pu(IV)] on -log [H+] with slope -2, in accord with LIBD. The solubility for Pu(IV) measured with LIBD is close to the lower limit of the solubility curve from previously reported data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
109
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(131 citation statements)
references
References 34 publications
(39 reference statements)
20
109
2
Order By: Relevance
“…[13,14] Plutonium L 3 extended X-ray absorption fine structure (EXAFS) data have been analyzed using a distribution of PuÀO bond lengths that are interpreted as Pu À O, Pu À OH, and Pu À OH 2 linkages and have been discussed within the standard model of Pu colloid formation through olation and dehydration reactions. [12,15] Laser-induced breakdown detection (LIBD) experiments on some of the samples used in the EXAFS measurements characterize the mean particle size in the range from smaller than 5 nm (detection limit) to about 12 nm. Small-angle neutron scattering and X-ray diffraction show evidence of PuO 2 -like linear aggregates in solution, with a chain diameter of about 5 nm.…”
mentioning
confidence: 99%
“…[13,14] Plutonium L 3 extended X-ray absorption fine structure (EXAFS) data have been analyzed using a distribution of PuÀO bond lengths that are interpreted as Pu À O, Pu À OH, and Pu À OH 2 linkages and have been discussed within the standard model of Pu colloid formation through olation and dehydration reactions. [12,15] Laser-induced breakdown detection (LIBD) experiments on some of the samples used in the EXAFS measurements characterize the mean particle size in the range from smaller than 5 nm (detection limit) to about 12 nm. Small-angle neutron scattering and X-ray diffraction show evidence of PuO 2 -like linear aggregates in solution, with a chain diameter of about 5 nm.…”
mentioning
confidence: 99%
“…Based on the experimental results of DLS and EXAFS, Abdel-Fattah et al (2013) and Ekberg et al (2013) indicated decreased size of aged polymers. However, an opposite trend in their size was shown according to the results of DLS (Triay et al, 1991), XRD (Delegard, 2013), LIBD (Rothe et al, 2004), and ultracentrifuge (Ichikawa and Sato, 1984). In addition, different shapes and appearances of the polymers either aggregated or grown on mineral surfaces were observed (Thiyagarajan et al, 1990;Powell et al, 2011;Zavarin et al, 2012).…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…3 with o sp logK = − 58.5 ± 0.7 (Neck et al, 2007;Fujiwara and Kohara, 2008), and a multiply bound Pu-O structure (Conradson et al, 2004;Rothe et al, 2004). However, its environmental fate is not yet clear.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Despite the feature of XANES spectra for Pu sample corresponding to the Pu(IV), its normalized intensity is lower than for Pu(IV) aqueous solution. Earlier [19] it was demonstrated that normalized intensity of WL for Pu(IV) in the form of intrinsic colloids is less than that for Pu(IV) aqueous solution. The same observations were made for ZrO 2 nano-particles including the effect of particle size [20].…”
Section: Actinide Redox Speciation By Xps and Xanesmentioning
confidence: 99%
“…Intrinsic colloids are formed through the oxo-and hydroxo bridge formation between actinide atoms [8,9]. Rothe et al [10] used laser-induced breakdown detection and extended X-ray absorption fine structure (EXAFS) to detect and probe intrinsic colloids that were present in equilibrium with Pu(OH) 4 even at relatively low pH values. The formation of intrinsic colloids is possible in the near-field conditions of the nuclear repository site, where the concentration of actinides could be high.…”
Section: Introductionmentioning
confidence: 99%